2018
DOI: 10.1155/2018/1950529
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Soil Moisture from Multiple Sources during 1988–2010 in the Yellow River Basin, China

Abstract: Soil moisture is a key variable in terrestrial water cycle, playing a key role in the exchange of water and energy in the landatmosphere interface. The spatiotemporal variations of soil moisture from multiple sources during 1988-2010 are evaluated against in situ observations in the Yellow River basin, China, including the Essential Climate Variable satellite's passive microwave product (SM ECV ), ERA-Interim reanalysis (SM ERA ), the National Centers for Environmental Prediction/Department of Energy's Reanaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Some earlier studies have reported on the strengths and weaknesses of various reanalysis and model-based soil moisture products over some regions in China [29,36,40,41]. These studies demonstrated the potential of these products to serve as reliable sources of long-term soil moisture variability and their potential applications in research and operational services due to their consistency in space and time.…”
Section: Discussionmentioning
confidence: 94%
“…Some earlier studies have reported on the strengths and weaknesses of various reanalysis and model-based soil moisture products over some regions in China [29,36,40,41]. These studies demonstrated the potential of these products to serve as reliable sources of long-term soil moisture variability and their potential applications in research and operational services due to their consistency in space and time.…”
Section: Discussionmentioning
confidence: 94%
“…Based on the present findings, CLDAS SM data were regarded appropriate for China's arid and semiarid zones. Previous studies have described the advantages and disadvantages of different reanalysis and modelbased SM products for some regions of China [76], [77], [78], [79].…”
Section: Discussionmentioning
confidence: 99%